Rainfall thresholds for flood warning in urban catchments considering spatial distribution of rainfall - Ali Nasiri; Esmaeil Salimi; Morteza Delfan Azari; Jafar Yazdi (Hydrological Sciences Journal, 2026)

Sero-evidence of Latent Toxoplasma Gondii Infection in Cancer Patients Before and After Chemotherapy, Northern Iran - Ramin Shekarriz; Nakisa Azari Noor; Zahra Hosseininezhad; Eisa Nazar; Mohammad Eslami Jouybari; Ehsan Zaboli; Maryam Ghasemi; Ali Sharifpour; Mahdi Fakhar (Acta Parasitologica, 2026)

Retraction notice to ‘Statistical modeling and optimization of dexamethasone adsorption from aqueous solution by Fe3O4@NH2-MIL88B nanorods: Isotherm, Kinetics, and Thermodynamic’ [Environ. Res. 236 (2023) 116773] - Mohammad Hassan Mahmoudian; Ali Azari; Anis Jahantigh; Maryam Sarkhosh; Mahmood Yousefi; Seyed Ali Razavinasab; Maryam Afsharizadeh; Fatemeh Mohammadi Shahraji; Abbas Pour Pasandi; Ali Zeidabadi; Tayebeh Ilaghinezhad Bardsiri; Mohammad Ghasemian (Environmental Research, 2026)

Economic evaluation of antibody-drug conjugates (ADCs) in patients with breast cancer: systematic review - Mohammad Ali Rezaei; Hamid Pourasghari; Fereshte Karimi; Soheila Rajaie; Amirreza Shahmohammady; Masoud Behzadifar; Amir Hossein Dehqan; Samad Azari (European Journal of Clinical Pharmacology, 2025)

Optimizing mixing duration to achieve efficient nitrite accumulation and functional microbiome enrichment in mainstream partial denitrification - Naveed Ali; Dara Memarzadeh; Anh Van Le; Jafar Ali; Stephan Fuchs; Mohammad Azari (Journal of Environmental Chemical Engineering, 2025)

Proliferating and migrating effects of regenerating sea anemone Aulactinia stella cells-derived exosomes on human skin fibroblasts - Nazanin Jafari; Alireza Afshar; Afshin Zare; Aria Salehpour; Alireza Hashemi; Fatemeh Zendehboudi; Zohreh Farrar; Mahdi Mahdipour; Arezoo Khoradmehr; Firouzeh Jahanfar; Nadiar M. Mussin; Asset A. Kaliyev; et al. (Natural Product Research, 2025)

Diatom assemblages in coral patches of the Northwestern Persian Gulf: Community structure across substrates and proximity to oil sites - Mahtab Azari; Ali Nasrolahi; Mohammad Reza Shokri; Roksana Majewska (Deep Sea Research Part II: Topical Studies in Oceanography, 2025)

Combined electrochemical conversion and micro-scale ZVI for enhanced energy production from anaerobic digestion of landfill leachate: Microorganisms survival and operational performance - Hasan Pasalari; Behnaz Abdollahinejad; Ali Azari; Seyed Nosratolah Taghavi; Mahdi Farzadkia; Tejraj M. Aminabhavi (Journal of Environmental Management, 2025)

Echocardiographic and clinical effects of two sedative doses of Dexmedetomidine in healthy horses - Ali Roustaei; Majid Masoudifard; Omid Azari; Hadi Keshipour; Omid Koohestani (Journal of Equine Veterinary Science, 2025)

The cost-effectiveness analysis of semaglutide for the treatment of adult and adolescent patients with overweight and obesity: a systematic review - Ali Sarabi Asiabar; Mohammad Ali Rezaei; Dariush Jafarzadeh; Soheila Rajaei; Pezhman Atefimanesh; Samira Soleimanpour; Mohammad Hossein Kafaei Meher; Samad Azari (European Journal of Clinical Pharmacology, 2024)

A New Flexible and Widely Software to Achieve Sustainable Agriculture based on Water-Energy-Food Nexus - Rezvan Khosravi; Arash Azari; Ali Bafkar (Water Resources Management, 2024)

Using water-energy-food nexus in agricultural management and sustainability by water management approach in Oshtorinan plain - Rezvan Khosravi; Ali Bafkar; Arash Azari (Environment, Development and Sustainability, 2024)

Characteristics of Microplastics in a Hospital Wastewater Treatment Plant Effluent and Hazard Risk Assessment - Hossein Kamani; Mehdi Ghayebzadeh; Ali Azari; Fatemeh Ganji (Environmental Processes, 2024)

RETRACTED: Statistical modeling and optimization of dexamethasone adsorption from aqueous solution by Fe3O4@NH2-MIL88B nanorods: Isotherm, Kinetics, and Thermodynamic - Mohammad Hassan Mahmoudian; Ali Azari; Anis Jahantigh; Maryam Sarkhosh; Mahmood Yousefi; Seyed Ali Razavinasab; Maryam Afsharizadeh; Fatemeh Mohammadi Shahraji; Abbas Pour Pasandi; Ali Zeidabadi; Tayebeh Ilaghinezhad Bardsiri; Mohammad Ghasemian (Environmental Research, 2023)

Effect of the interaction of nisin Z with various polysaccharides on its antibacterial activity - Mojtaba Azari-Anpar; Pascal Degraeve; Sandrine Ecochard; Kambiz Jahanbin; Ali Assifaoui; Isabelle Adt; Yann Demarigny; Farideh Tabatabaei Yazdi; Nadia Oulahal (Food Control, 2023)

A GIS-based approach for accident hotspots mapping in mountain roads using seasonal and geometric indicators - Mehdi Azari; Ali Paydar; Bakhtiar Feizizadeh; Vahid Gara Hasanlou (Applied Geomatics, 2023)

Application of multi-objective genetic algorithm for optimal combination of resources to achieve sustainable agriculture based on the water-energy-food nexus framework - Faranak Karamian; Ali Asghar Mirakzadeh; Arash Azari (Science of The Total Environment, 2023)

Extracting Optimal Rule Curve of Dam Reservoir Base on Stochastic Inflow - Ali Jalilian; Majeid Heydari; Arash Azari; Saeid Shabanlou (Water Resources Management, 2022)

Nanotechnology-based products for cancer immunotherapy - Forough Shams; Ali Golchin; Arezo Azari; Leila Mohammadi Amirabad; Fateme Zarein; Atiyeh Khosravi; Abdolreza Ardeshirylajimi (Molecular Biology Reports, 2022)

Forecast and risk analysis of floodplain regarding uncertainty factors - Elham Jokar; Ali Arman; Arash Azari (Natural Hazards, 2021)

Stem Cell Therapy Potency in Personalizing Severe COVID-19 Treatment - Arefeh Basiri; Fatemeh Mansouri; Arezo Azari; Parviz Ranjbarvan; Fateme Zarein; Arash Heidari; Ali Golchin (Stem Cell Reviews and Reports, 2021)

Green preparation of activated carbon from pomegranate peel coated with zero-valent iron nanoparticles (nZVI) and isotherm and kinetic studies of amoxicillin removal in water - Imran Ali; Shirin Afshinb; Yousef Poureshgh; Ali Azari; Yousef Rashtbari; Abolfazl Feizizadeh; Asghar Hamzezadeh; Mehdi Fazlzadeh (Environmental Science and Pollution Research, 2020)

Modeling and optimizing parameters affecting hexavalent chromium adsorption from aqueous solutions using Ti-XAD7 nanocomposite: RSM-CCD approach, kinetic, and isotherm studies - Sahar Sharifi; Ramin Nabizadeh; Bahman Akbarpour; Ali Azari; Hamid Reza Ghaffari; Shahrokh Nazmara; Babak Mahmoudi; Leila Shiri; Mahmood Yousefi (Journal of Environmental Health Science and Engineering, 2019)

Degradation of dimethyl phthalate using persulfate activated by UV and ferrous ions: optimizing operational parameters mechanism and pathway - Mojtaba Yegane Badi; Ali Esrafili; Hasan Pasalari; Roshanak Rezaei Kalantary; Ehsan Ahmadi; Mitra Gholami; Ali Azari (Journal of Environmental Health Science and Engineering, 2019)

Desorption kinetics and isotherms of phenanthrene from contaminated soil - Farzaneh Gharibzadeh; Roshanak Rezaei Kalantary; Ali Esrafili; Masoumeh Ravanipour; Ali Azari (Journal of Environmental Health Science and Engineering, 2019)

Prevalence and probabilistic health risk assessment of aflatoxins B1, B2, G1, and G2 in Iranian edible oils - Samaneh Nabizadeh; Nabi Shariatifar; Esmail Shokoohi; Shahram Shoeibi; Mohsen Gavahian; Yadolah Fakhri; Ali Azari; Amin Mousavi Khaneghah (Environmental Science and Pollution Research, 2018)

Insights into the roles of anammox bacteria in post-treatment of anaerobically-treated sewage - Qian Wang; Giin-Yu Amy Tan; Mohammad Azari; Xiaowu Huang; Martin Denecke; Yujie Men; Jin-Young Jung; Satoshi Okabe; Muhammad Ali; Yu-Tzu Huang; Zhuoying Wu; Wai-hung Lo; et al. (Critical Reviews in Environmental Science and Technology, 2018)

Enhanced chromium (VI) removal using activated carbon modified by zero valent iron and silver bimetallic nanoparticles - Babak Kakavandi; Roshanak Rezaei Kalantary; Mahdi Farzadkia; Amir Hossein Mahvi; Ali Esrafili; Ali Azari; Ahmad Reza Yari; Allah Bakhsh Javid (Journal of Environmental Health Science and Engineering, 2014)
Recently, adsorption process has been introduced as a favorable and effective technique for the removal of metal ions from aqueous solutions. In the present study, bimetallic nanoparticles consisting of zero valent iron and silver were loaded on the activated carbon powder for the preparation of a new adsorbent (PAC-Fe o /Ag). The above adsorbent was characterized by using XRD, SEM and TEM techniqes. Experimental data were exploited for kinetic, equilibrium and thermodynamic evaluations related to the adsorption processes. The Cr(VI) adsorption process was found to be favorable at pH 3 and it reached equilibrium state within 60 min. The stirring rate did not have a significant effect on the adsorption efficiency. Furthermore, the monolayer adsorption capacity of Cr(VI) based on the Langmuir model was measured to be 100 mg/g. The experimental equilibrium data were fitted to the Freundlich adsorption and pseudo second-order models. According to the thermodynamic study, the adsorption process was spontaneous and endothermic in nature, indicating the adsorption capacity increases with increasing the temperature. The results also revealed that the synthesized composite can be potentially applied as a magnetic adsorbent to remove Cr(VI) contaminants from aqueous solutions.

SUBSURFACE DRAINAGE IN KHUZESTAN, IRAN: ENVIRONMENTALLY REVISITED CRITERIA - Mojtaba Akram; Ardavan Azari; Ali Nahvi; Zahra Bakhtiari; Heydar D. Safaee (Irrigation and Drainage, 2013)
Khuzestan, a south‐western province of Iran with a hot climate, long growing season and lots of water, is the main region of subsurface drainage. Sugar cane is the major artificially drained crop. In the past, drainage rates had been chosen based on highest water‐consuming crop in the cropping pattern. This approach neglects crops with less water demands, natural drainage and direct flow towards perforated collectors or open deep drains, and soil water reservoirs. The drains are installed deeply which bring more saline drainage water out of the underlying strata into the environment. The environmental problems are due to the high volume of very poor quality drainage water. The low irrigation efficiency results in a high volume of drainage water. Deeper drains are also responsible for over‐drainage because they usually work longer and bring mined salt water out of the deeper strata. This paper attempts to show that in arid areas with a long irrigation season and/or high deep percolation one does not have to expect secondary salinization provided that the leaching requirement is met. Maintaining higher irrigation efficiency, installation of shallower drains and the application of controlled drainage are measures to reduce salt removal, and hence reduce environmental hazards. Copyright © 2013 John Wiley & Sons, Ltd.

Development of pH-sensitive Insulin Nanoparticles using Eudragit L100-55 and Chitosan with Different Molecular Weights - Mitra Jelvehgari; Parvin Zakeri-Milani; Mohammad Reza Siahi-Shadbad; Badir Delf Loveymi; Ali Nokhodchi; Zahra Azari; Hadi Valizadeh (AAPS PharmSciTech, 2010)